A COMPREHENSIVE REVIEW OF SOFTWARE DEVELOPMENT METHODOLOGIES: MODELS, MINDSET, AND MISUNDERSTANDINGS - Muhammad Zeeshan Haider Ali; Abdulrehman Arif; Syed Zohair Quain Haider; Muhammad Azam; Mubasher H Malik; Ammad Hussain (Spectrum of Engineering Sciences, 2025)
Software development has evolved from highly structured models to more flexible, adaptive methodologies. This paper reviews key software development techniques, including traditional models like the Waterfall approach, as well as modern frameworks such as Agile, DevOps, and AI-assisted methodologies. A comprehensive analysis of over 50 peer-reviewed articles is conducted, encompassing both historical and contemporary approaches to software development. The literature review is structured chronologically to highlight the progression of Software Development Methodologies (SDMs), enabling readers to track the evolution of these techniques over time. A detailed comparison table is presented to assist in understanding the advantages, limitations, and applications of each methodology. The objective of this review is to guide researchers and practitioners in selecting the most suitable SDM for dynamic, evolving project requirements. Software Development Methodologies (SDMs), Agile and Traditional Models, Hybrid Approaches, DevOps and AI-driven Methods, Methodological Misconceptions